The communicative content of "Israeli" popular diplomacy from the perspective of international public relations - Kyoosh, Khalaf Kareem; Muhammad, Arrak Ghanem (ALBAHITH ALALAMI, 2021)
This study deals with the conceptual rooting of the practical relationship between the practice of international public relations and popular diplomacy, as the latter sought - as a legitimate extension of traditional diplomacy - to involve foreign residents in international public relations capable of drawing a positive image of the state among people of other countries, by employing modern communication technology. Especially social media, which led to a shift from old diplomacy to digital public diplomacy. The research paper seeks to analyze the communicative content of the Facebook page (Israel in the Iraqi dialect), which a page is belonging to the "Israeli" Ministry of Foreign Affairs that aims, according to its messages, to encourage dialogue between "Israelis" and Iraqis. The study aims to know the methods and tactics that "Israel" used in its communication contents to market it to the public Iraqi. Therefore, the researchers used the descriptive approach and the content analysis method to analyze the communicative content of popular diplomacy via Facebook, for the period from 8/13/2020 to 10/13/2020. The two researchers reached a set of results, the most important of which is that "Israel" used social networking sites in a manner appropriate to build its image in front of other people, especially the Iraqi people, by focusing on the topic of "Iraqi-Jewish rapprochement" and using the Iraqi dialect .